2007
DOI: 10.1038/sj.leu.2404776
|View full text |Cite
|
Sign up to set email alerts
|

BH3 mimetic ABT-737 neutralizes resistance to FLT3 inhibitor treatment mediated by FLT3-independent expression of BCL2 in primary AML blasts

Abstract: FLT3 defines a promising target for the treatment of acute myeloid leukemia (AML). In contrast to their efficacy in cell lines, FLT3-specific inhibitors as single agents have only modest clinical activity in patients with AML. As demonstrated here, overexpression of anti-apoptotic proteins of the BCL2 family leads to resistance against FLT3 inhibitors in a hematopoietic cell line model with activating FLT3 mutations. The susceptibility to FLT3 inhibition could be restored by treatment with the novel BH3 mimeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 45 publications
2
66
0
Order By: Relevance
“…This result is consistent with a previous observation. 33 Taken together, our results suggest that mitochondrial apoptotic pathways can be important in cell death induction by the FI-700/Nutlin-3 combination.…”
Section: Flt3 Inhibition By Fi-700 Induces G 1 -Phase Cell-cycle Arresupporting
confidence: 51%
See 1 more Smart Citation
“…This result is consistent with a previous observation. 33 Taken together, our results suggest that mitochondrial apoptotic pathways can be important in cell death induction by the FI-700/Nutlin-3 combination.…”
Section: Flt3 Inhibition By Fi-700 Induces G 1 -Phase Cell-cycle Arresupporting
confidence: 51%
“…42,43 The strategies that target Mcl-1 have been found to sensitize many cell types to ABT-737, 42,43 which would be applicable to AML with activating FLT3 mutations. 33 Because TP53 mutations are rare in AML, most patients with activating FLT3 mutations can potentially benefit from combination treatment with FLT3 inhibitor and p53-activating agents (for example, Nutlins, anthracyclines, alkylating agents, topoisomerase inhibitors and so on). It has been reported that a proportion of patients harboring FLT3 mutations exhibit primary resistance to FLT3 inhibitor treatment, although the precise mechanisms are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…ABT-737 has demonstrated killing potency in combination settings in cell line-based models (11)(12)(13)(14)(15)(16)(17). Furthermore, the potency of ABT-737 with diverse chemotherapeutic agents has been shown in the case of primary leukemia cells and in small-cell lung cancer (SCLC) primary xenografts (18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…For example, increased protein levels of the inhibitor of apoptosis (IAP), survivin, as well as activation of STAT1, STAT3 and STAT5, were observed in ABT-869-resistant MV4-11 cells (Zhou et al, 2009), and antiapoptotic proteins were upregulated in PKC412-resistant MV4-11 cells (Stolzel et al, 2010). Similarly, overexpression of antiapoptotic proteins of the BCL2 family has been found to mediate resistance to FLT3 inhibition in hematopoietic cells with activating FLT3 mutations Mechanisms of resistance to FLT3 inhibition E Weisberg et al (Kohl et al, 2007) and the antiapoptotic protein, MCL-1, was observed to be induced by a non-juxtamembrane ITD that has integrated into the b-2 sheet of the first kinase domain (FLT3_ITD627E) (Brietenbuecher et al, 2009). In association with expression of FLT3-ITD and tyrosine kinase domain mutation dual mutants, which occurs in 1-2% of mutant FLT3-positive patients, there is induction of tyrosine kinase inhibitor and daunorubicin resistance through hyperactivation of STAT5 and consequent upregulation of Bcl-x(L) (Bagrintseva et al, 2005).…”
Section: Aberrant Activation Of Growth and Viability Pathwaysmentioning
confidence: 99%